Review of traceability system applications. Case study: the wiring harness industry - León-Duarte, Jaime Alfonso; De La Re-Iñiguez, Blanca Melissa (Estudios de Administración, 2020)
The purpose of this research is to develop a methodology for improving a wiring harness production process that allows for tracing the products that are processed in a specific area - in this case in a foam injection operation - by implementing a bar-coded electronic monitoring system. The steps involved in this methodology are as follows: a prior analysis of the area; development of a traceability program; implementation of the system and, finally, evaluation of the results. Thanks to the information obtained through the new traceability system, the main defects in the area were identified and specific actions were taken to minimize their recurrence, achieving a 23% reduction of defects after one month of trials.